Counseling to Students of SMA Muhammadiyah 2 Palangka Raya City Regarding Online and Wise Gambling in Social Media Perspective Law No. 1 of 2024 - Ahmidi, Ahmidi; Alhamdani, Alhamdani; Aldo Yanuarto, Aldo Yanuarto; Muhammad Luthfi Setiarno Putera, Muhammad Luthfi Setiarno Putera; Yuliana Fatmawati, Yuliana Fatmawati; Luqman Hakim, Luqman Hakim; Muhammad Sahdan Siregar, Muhammad Sahdan Siregar (Jurnal Pengabdian Masyarakat Bestari, 2024)
The main objective of this counseling is to raise students' awareness about the dangers of online gambling and the importance of being wise when using social media. Presentations, discussions, were used to engage students in this activity. Starting from the rise of online gambling cases in Indonesia, the results of the activity show that students better understand the adverse effects of online gambling and the associated legal consequences. In addition, students showed greater awareness on how to use social media properly.